Impact of smoking status and smoking cessation after coronary revascularization on long-term clinical outcomes: from a nationwide population-based study. (25th November 2020) - Ki, Y.J; Han, J.K; Lee, H.S; Chang, M.O; Kang, J.H; Yang, H.M; Park, K.W; Kang, H.J; Koo, B.K; Kim, H.S
Abstract: Background: There are many studies on emphasizing the importance of quitting smoking, but the smoking status was based on baseline status without subsequent status. Since a significant percentage of patients who have received coronary revascularization change their smoking status, it is necessary to confirm the clinical consequences of smoking status after revascularization. Purpose: In this study, we aimed to investigate the impact of smoking status after revascularization on long-term clinical outcomes, using large population based study from the Korean National Health Insurance System. Methods: Among 74, 004 patients who received coronary revascularization (PCI or CABG) from 1 January 2007 to 21 December 2013 and underwent regular health check-up within 2 years after index PCI, examined for death, MI, revascularization and stroke. Results: Within patients who underwent revascularization, 33, 800 (45.7%) of patients were self-reported non-smoker, 28, 603 (38.7%) were ex-smoker, 11601 (15.6%) were current smokers at first regular health check-up after revascularization. Current smokers were associated with higher risks for death (HR: 1.497; 95% CI: 1.366–1.641), MI (HR: 1.498; 95% CI: 1.302–1.723) and revascularization (HR: 1.088; 95% CI: 1.018–1.164) than non-smokers. Compared with non-smokers, more than 30PY ex-smokers and current smokers showed higher incidence of major adverse cardiovascular and cerebrovascular events (MACCE), defined as a composite of death, MI, revascularization and stroke. Regarding smoking tendency, maintaining non-smokers were lower risk for MACCE than maintaining smokers (Figure 1). Quitters tended to lower MACCE compared to patients who continued to smoke (HR: 0.823; 95% CI: 0.762–0.888). Especially, maintaining non-smokers and quitters significantly showed lower mortality than patients who continued to smoke. Conclusion: Smoking is associated with poor clinical outcomes after coronary revascularization especially more than 30PY ex-smokers and current smokers. These results also emphasized that smoking cessation after revascularization also important for mortality benefit. Funding Acknowledgement: Type of funding source: None